Analysis of the Effectiveness of Financial Management and its Implications for Society (Case Study in Su'rulangi Village, Takalar Regency) - Rismayanti (Mustard Journal De Ecobusin, 2024)
This paper set out to discuss the efficacy of the financial management and its implication to the society by using Su’rulangi Village in Takalar Regency as the case study. The study employed a qualitative approach utilizing eight informants who were recruited among the representatives of the government and the community members. The information was gathered using interviews and documents whereas analysis was done descriptively. The results indicate that financial management in Su’rulangi Village is mostly carried out according to the relevant regulations and set standards. This can be seen in the planning, implementation, reporting, administration and accountability stages. Practically, it was established that multiple aspects affected the success of the Village Fund management, and they included communication, resources at hand, disposition, and bureaucracy. The achievement of goals, timeline adherence, easy disbursement, and proper utilization of funds to plan activities was effectiveness. The positive implications to the local community are also brought out in the study. The management at Village Fund helped in economic growth by giving the loans in the form of agricultural assistance (seeds, plant sprayers, and water pumps) and social assistance programs (BLT and PKH) during the COVID-19 pandemic.